Assessing the impact of servant leadership on employee engagement through the mediating role of self-efficacy in the Pakistani banking sector - Zeeshan, Sobia; Ng, Siew Imm; Ho, Jo Ann; Jantan, Amer Hamzah; Gupta, Manish (Cogent OA, 2021)
The purpose of conducting this research is to investigate the impact of servant leadership (SL) on employee engagement (EE) through the mediating role of self-efficacy (SE) among Pakistani bank employees. The literature suggests that servant leadership leads to increased self-efficiency, which in turn enhances employee engagement. However, the direct and indirect relationship between this leadership style and employee engagement remains under-researched. The purpose of this research was therefore to investigate the impact of servant leadership on Pakistani bank employees’ engagement through the mediating role of self-efficacy. Survey data was collected from public and private bank employees using the multistage sampling method. Data analysis using SmartPLS revealed that servant leadership has a direct positive impact on employee engagement. The mediating role of self-efficacy between this relationship was also found to be positive and significant, in line with the conservation of resources theory. Thus, bank managers should practice servant leadership in interacting with their employees to improve the latter’s involvement in their jobs.